MERS CoV Infection in Two Renal Transplant Recipients: Case Report. Issue 4 (25th February 2015) - AlGhamdi, M.; Mushtaq, F.; Awn, N.; Shalhoub, S.
Abstract : Middle East Respiratory Syndrome Coronavirus (MERS CoV) infection has recently emerged as a cause of severe potentially fatal pneumonia. The clinical presentation ranges from asymptomatic infection to severe pneumonia and acute renal failure. Data on the clinical presentation in solid organ transplant recipients are lacking. We report two cases of MERS CoV infections in two renal transplant recipients with variable clinical presentations and outcomes. The first patient presented with progressive respiratory symptoms, acute renal failure and died. While the second patient presented with respiratory tract symptoms, remained stable and had an excellent clinical recovery despite recent reception of thymoglobulin induction. This is a rare report of MERS CoV infection in renal transplant recipients. Further data are needed to gain better understanding of the impact of anti‐rejection immunosuppressive therapy on the clinical presentation, severity and outcome of MERS CoV infections in solid organ transplant recipients. Abstract : The authors report on two kidney transplant recipients with confirmed Middle East Respiratory Syndrome infection, with death in one case and successful recovery in the other, and the measures taken by the kidney transplant program to limit the spread among solid organ transplant recipients.